Participation in the Company of HBK-Spaarbank - Lambrechts, M. (Journal of business ethics, 1999)
This paper relates the origin, the principles and the evolution of the financial participation in HBK-Spaarbank. This participation in the capital is concretized by the cooperative company Personnel Cooperative HBK. Founded in 1979, this cooperative company which represents all workers of HBK-Spaarbank has now become a very significant shareholder. At present it owns 22.50 % of the capital of the savings bank.